PINGA-FOGO COM CHICO XAVIER: DO ETHOS À SEMÂNTICA GLOBAL DO DISCURSO ESPÍRITA KARDECISTA - Silva, Tamiris Vianna Da; Brunelli, Anna Flora (Universidade do Sul de Santa Catarina, 2016)
Abstract Considering the reflections developed by Maingueneau (2001, 2005, 2006 and 2008) on the notion of discursive ethos, in this paper we analyze the ethos of the medium Francisco Cândido Xavier on the book Pinga-Fogo com Chico Xavier, in order to contribute to the studies of the kardecist spiritualist discourse, one of the religious discourses which are circulating in Brazil. For this analysis we observe specially the lexicon of occurrences concerning 3 types of ethos: the pre-discursive ethos, the said ethos and shown ethos. We identify not only the image of the discourse's guarantor, but also the scene of enunciation in which this guarantor emerges. Finally, we demonstrate how the ethos of the medium Chico Xavier is linked to the global semantics of the kardecist spiritualist discourse.

Resumen Considerando reflexiones desarrolladas por Maingueneau (2001, 2005, 2006, 2008) sobre la noción de ethos discursivo, se analiza, en este trabajo, el ethos del médium Francisco Cândido Xavier en la obra Pinga-Fogo com Chico Xavier. El objetivo es contribuir con los estudios sobre el discurso espiritista kardecista, uno de los discursos religiosos que existen en Brasil. Para ello, se observa especialmente el léxico de ocurrencias relativas con el ethos pre-discursivo, con el ethos dicho y con el ethos mostrado, que permite identificar no solo el perfil del fiador del discurso, pero también la escena de enunciación en que ese fiador emerge. Al fin se demuestra como el ethos del médium está vinculado con la semántica global del discurso espiritista kardecista.

Resumo Considerando as reflexões desenvolvidas por Maingueneau (2001, 2005, 2006, 2008) sobre a noção de ethos discursivo, analisa-se, neste trabalho, o ethos do médium Francisco Cândido Xavier na obra Pinga-Fogo com Chico Xavier, com o intuito de contribuir com os estudos sobre o discurso espírita kardecista, um dos discursos religiosos que há no Brasil. Para tanto, observa-se especialmente o léxico de ocorrências relativas ao ethos pré-discursivo, ao ethos dito e ao ethos mostrado, o que permite identificar não só o perfil do fiador do discurso, mas também a cena de enunciação em que esse fiador emerge. Por fim, demonstra-se como o ethos do médium está vinculado à semântica global do discurso espírita kardecista.
Pinga-fogo com Chico Xavier: from the ethos to the global semantics of the kardecist spiritualist discourse
Pinga-fogo com Chico Xavier: del ethos hasta la semántica global del discurso espiritista kardecista
Keywords: Discourse; Spiritualism; Global semantics; Ethos; Enunciation scene.; Discurso; Espiritismo; Semântica global; Ethos; Cena de enunciação.